PERBEDAAN PERILAKU PEDULI LINGKUNGAN PESERTA DIDIK BERDASARKAN GENDER DI SMAN 1 2X11 KAYUTANAM TAHUN PELAJARAN 2020/2021 - Ranti Wulan Sari; Ernawati ernawati (JURNAL GEOGRAFI, 2021)
ABSTRACT This purposeof this study is to describe, analyze and discuss data on: Differences in students' environmental care behavior based on gender at SMAN 1 2x11 Kayutanam in the 2020/2021 school year. The approach used in this research is descriptive quantitative with the type of research used is Expost facto research. The population of this study were students at SMAN 1 2X11 Kayutanam for the academic year 2020/2021, totaling 400 students. The sample of this research was done by simple random sampling with a total sample of 61 students. Data collection techniques used are questionnaires and documentation.The data analysis technique used is the respondent achievement level data analysis technique (TCR) and t-test. The results showed that: 1) The environmental concerns of male students had a significant difference with the environmental concerns of female students. Environmental awareness of female students is higher than that of male students. The criteria for the environmental care behavior of students belong to the caring category. 2) Hypothesis test results obtained t-count > t-table of (79.1685 > 1.65765 ), at a significant level 0.05. The results of hypothesis testing are accepted (H0 is rejected and H1 is accepted). Keywords : environmental care behavior, gender